USING WATTPAD APLICATION TOWARDS STUDENTS’ READING COMPREHENSION - Salam, Naimul (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2022)
the development of the current era is changing so fast that students and teachers get so much convenience from the availability of electronic media, one of which is wattpad media. Wattpad is a platform that provides various stories, articles or poems in English online and offline. Wattpad was created by Allen Lau and Ivan Yuen in 2006. In Indonesia, the results of data taken from the Progress of International Reading Literacy Study (PIRLS, 2011) also show that Indonesia is ranked 41st out of 45 countries. This case has become commonplace in Indonesia due to the lack of interest in reading and special attention from the Indonesian government. From the availability of the Wattpad application which has interesting stories and is easy to access by anyone, is it so that reading interest, especially in Indonesia, through the data collected, makes reading interest and understanding in reading increase.